2012
DOI: 10.1155/2012/164219
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Trigonelline on Experimental Diabetic Peripheral Neuropathy

Abstract: The mechanisms leading to diabetic peripheral neuropathy are complex and there is no effective drug to treat it. As an active component of several traditional Chinese medicines, trigonelline has beneficial effects on diabetes with hyperlipidemia. The protective effects and the mechanism of trigonelline on diabetic peripheral neuropathy were evaluated in streptozotocin- and high-carbohydrate/high-fat diet-induced diabetic rats. Rats were divided into four groups at the end of week 2: control, diabetes, diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 52 publications
6
22
0
Order By: Relevance
“…Moreover, insulin, HOMA‐IR and altered lipid profile were corrected. These results match previous findings in diabetic and insulin‐resistant rats . The current work verified the involvement of the crucial insulin signalling pathway in the antihyperglycemic effect of TRG.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, insulin, HOMA‐IR and altered lipid profile were corrected. These results match previous findings in diabetic and insulin‐resistant rats . The current work verified the involvement of the crucial insulin signalling pathway in the antihyperglycemic effect of TRG.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with a previous study that has reported increased pain sensitivity following sitagliptin administration for 35 days in STZ-nicotinamide-induced diabetic neuropathy in rats [42]. However, another study has reported that administration of sitagliptin for 48 weeks significantly reversed the decrease in tail-flick latencies in STZ-induced diabetic animals [43]. Therefore, further studies are required to comment on the presumptive role of sitagliptin in the prevention/delay of progression of diabetic neuropathy.…”
Section: Discussionsupporting
confidence: 92%
“…In the current investigation, male rats was employed as an experimental model due to male rodents' lack of hormonal fluctuation, which makes developing metabolic disease less difficult than in female rats. Moreover, the STZ model of diabetic morin treated, compared with diabetic untreated group DN used in the current and several other experimental investigations, is standardized against numerous reference anti-diabetic drugs such as glibenclamide and sitagliptin [27,28] as well as antineuropathic pain medications such as pregabalin [29].…”
Section: Discussionmentioning
confidence: 99%